2018
DOI: 10.1088/1475-7516/2018/06/007
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look into the interacting dark matter scenario

Abstract: The elastic scattering between dark matter particles and radiation represents an attractive possibility to solve a number of discrepancies between observations and standard cold dark matter predictions, as the induced collisional damping would imply a suppression of small-scale structures. We consider this scenario and confront it with measurements of the ionization history of the Universe at several redshifts and with recent estimates of the counts of Milky Way satellite galaxies. We derive a conservative upp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 212 publications
(408 reference statements)
2
57
1
Order By: Relevance
“…This effect leads to a suppression of the amount of small scale structures today. By comparing LSS predictions to observations, one can set an upper bound on the strength of the elastic scattering between DM and neutrinos [8,78]. Nevertheless, for the models we are presenting in this work, the mixing between the sterile and SM neutrino suppresses the neutrino-DM elastic scattering and, consequently, its effect on LSS constrains regions of the parameter space already ruled out by CMB and BBN constraints [14].…”
Section: Constraints From Cosmologymentioning
confidence: 88%
“…This effect leads to a suppression of the amount of small scale structures today. By comparing LSS predictions to observations, one can set an upper bound on the strength of the elastic scattering between DM and neutrinos [8,78]. Nevertheless, for the models we are presenting in this work, the mixing between the sterile and SM neutrino suppresses the neutrino-DM elastic scattering and, consequently, its effect on LSS constrains regions of the parameter space already ruled out by CMB and BBN constraints [14].…”
Section: Constraints From Cosmologymentioning
confidence: 88%
“…[43,44,58,59]. As a result a shift to later times in the typical features in the 21 cm sky-averaged global signal and power spectrum is observed in the context of non-cold dark matter [58,59,[77][78][79]. Consequently, it is timely to study the compatibility between the observation reported by EDGES, located at a redshift around z 17 and the IDM scenario.…”
Section: Introductionmentioning
confidence: 90%
“…While NCDM scenarios are unlikely to explain the large absorption amplitude, they delay structure formation and, therefore, might delay the onset of reionization and of UV and X-ray emission, see e.g. [43,44,58,59]. As a result a shift to later times in the typical features in the 21 cm sky-averaged global signal and power spectrum is observed in the context of non-cold dark matter [58,59,[77][78][79].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have studied the effect of non-CDM models on the 21-cm signal [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Those models typically suppress the matter power spectrum beyond some wavenumber k, delaying the onset of cosmic dawn.…”
Section: Introductionmentioning
confidence: 99%